Thermal Insulation of Buildings: A Synthesis of Approaches and Innovative Materials: ISBN 978-630-95064-5-0 - Ziad, Slimane (Technium Books, 2025)
The book: Thermal Insulation of Buildings: A Synthesis of Approaches and Innovative Materials is published in Technium.